Development and Implementation of the Independent Curriculum in "Penggerak" Kindergartens: A Case Study of Semarang City - Sulchaniya, Chilya; Waluyo, Edi (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
Implementing the Independent Curriculum in early childhood education presents challenges and opportunities, particularly in aligning curriculum design with local needs and ensuring stakeholder collaboration. This research examines the development and implementation of the Independent Curriculum in three "Penggerak" Kindergartens in Semarang City: TK ABA 54, TK Talenta, and TK Pertiwi 31. The study employs a descriptive qualitative method involving principals, teachers, supervisors, and parents and focuses on institutional readiness and stakeholder collaboration. Data collection was conducted through semi-structured interviews, observations, and document analysis. Findings reveal that each kindergarten developed a curriculum tailored to its unique institutional characteristics and student needs, with an emphasis on integrating national standards, local values, and religious principles. TK Talenta prioritized inclusive education for special needs children, while TK Pertiwi 31 focused on contextual learning approaches. Collaborative curriculum planning involving key stakeholders was a central strategy in all three institutions. Despite the successes, challenges emerged, particularly in teachers’ comprehension of the Independent Curriculum, which necessitated additional support through professional development. The study concludes that a flexible and contextually grounded curriculum fosters inclusivity and adapts to local needs in early childhood education. However, the limited geographic focus and short observation period challenge generalizing the findings. Future research should adopt longitudinal approaches to evaluate the curriculum's long-term impacts and explore interdisciplinary strategies in curriculum design.